Incidence of Stroke and Associated Risk Factors in Bogor, Indonesia: A Nested Case-Control Study - Saefurrohim, Muhamad Zakki; Azam, Mahalul; Rahayu, Sri Ratna; Cahyati, Widya Hary (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The increasing number of stroke cases and their risk factors is a crisis that needs to be addressed. This study aimed to determine the number of new stroke cases in Bogor, Indonesia, and its risk factors. We conducted a nested case-control study from the Study of Non-Communicable Disease (NCD) Risk Factors of the National Health Institute of Research and Development, Ministry of Health, Indonesia, in 2018. A deep analysis was conducted on 1.210 respondents based on the subset of baseline this data. Data was collected by interview method on permanent residents in Bogor City, Indonesia in 2018. Diagnosis of stroke was based on the anamnesis of a neurologist and a neurological examination. Independent variables include sociodemographic characteristics, metabolic syndrome, and risky behaviors. The data was analyzed with a dual logistic regression test. The incidence of stroke during 2018 amounted to 48 cases (3.9%). The main determinants of stroke in this population include diabetes mellitus and systolic blood pressure being the main factors for stroke, with each p-value, AOR, and (95% CI) being 0,000, 0.222 (0.122-0.405), 0.003, 0.291 (0.128-0.662). There was no significant difference in metabolic syndrome outcomes one year before the diagnosis of stroke and the year when the stroke was diagnosed. Special attention is needed in DM patients with high blood pressure to prevent stroke.